Synthesis, affinity for complementary RNA and DNA, and enzymatic stability of Triazole-linked locked nucleic acids (t-LNAs) - Kumar, P; Truong, L; Baker, Y; El-Sagheer, A; Brown, T (American Chemical Society, 2018)
Dinucleoside phosphoramidites containing a triazole internucleotide linkage flanked by locked nucleic acid (LNA) were synthesized and incorporated into oligonucleotides (ONs). ONs bearing both LNA and triazole at multiple sites were obtained and their biophysical properties including enzymatic stability and binding affinity for RNA and DNA targets were studied. t-LNAs with four incorporations of a dinucleoside monomer having LNA on either side of the triazole linkage bind to their RNA target with significantly higher affinity and greater specificity than unmodified oligonucleotides, and are remarkably stable to nuclease degradation. A similar but reduced effect on enzymatic stability and binding affinity was noted for LNA only on the 3'-side of the triazole linkage. Thus, by combining unnatural triazole linkages and LNA in one unit (t-LNA), we produced a promising class of ONs with reduced anionic charge and potential for antisense applications.